METODE KETELADANAN PERSPEKTIF AL-QUR’AN DALAM PENGUATAN KARAKTER PESERTA DIDIK SEKOLAH DASAR DAN MENENGAH - Putriyana Rahayu; Entis Sutisna; Hanifa Chaerani; Cecep Nasrul Yakin (Jurnal Genta Mulia, 2026)
Character education among elementary and secondary school students faces various serious challenges, particularly due to moral degradation, low discipline, intolerant behavior, misuse of social media, and weak internalization of moral values in daily life. These conditions indicate that character education has not been implemented optimally and remains dominated by academic orientation. This study aims to analyze the exemplary method from the Qur’anic perspective in strengthening students’ character, explain its normative and psychological foundations, and examine the effectiveness of its implementation in the context of contemporary education and the digital era. The study employed a Systematic Literature Review (SLR) approach using the PRISMA model through the stages of identification, screening, eligibility, and inclusion. Literature searches were conducted through Google Scholar, Garuda, DOAJ, and SINTA databases using keywords related to exemplary methods and character education. Out of 87 identified articles, 35 articles met the inclusion criteria and were further analyzed using content analysis techniques. The findings indicate that the exemplary method is effective in developing students’ discipline, responsibility, religiosity, integrity, social empathy, communication ethics, and learning motivation. The concept of uswah hasanah in the Qur’an also demonstrates strong relevance to Albert Bandura’s Social Learning Theory and Lawrence Kohlberg’s moral development theory. The novelty of this study lies in the integration of the Qur’anic perspective with modern educational psychology theories as well as the analysis of exemplary methods within the context of digital culture. This study concludes that the exemplary method constitutes a relevant and effective moral education paradigm for strengthening students’ character in the modern era.